Computational Vision and Medical Image Processing 2011
DOI: 10.1201/b11570-90
|View full text |Cite
|
Sign up to set email alerts
|

FRP strengthening of shear walls with openings

Abstract: Concrete shear walls are one of the main lateral resisting members in buildings. The functional requirements like architectural and even mechanical requirements entail that openings have to be installed in structural walls as well as floors. In this study, nonlinear static analysis was utilized to study the effects of fiber reinforced plastic (FRP) on the ultimate load capacity of concrete shear walls with openings using the finite element analysis software ABAQUS. In order to verify the accuracy of the numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…When conducting experimental tests, the technique would not continue until the wall was entirely destroyed and collapsed. The test would often continue until a peak strength decrease of between 75-80% was noticed, or it would be stopped if the test specimen exhibited the concrete spalling mode of failure [38,39]. In our research, the failure loads occurred either by the failure of GFRP sheets or by concrete crushing.…”
Section: Load Capacitymentioning
confidence: 88%
See 2 more Smart Citations
“…When conducting experimental tests, the technique would not continue until the wall was entirely destroyed and collapsed. The test would often continue until a peak strength decrease of between 75-80% was noticed, or it would be stopped if the test specimen exhibited the concrete spalling mode of failure [38,39]. In our research, the failure loads occurred either by the failure of GFRP sheets or by concrete crushing.…”
Section: Load Capacitymentioning
confidence: 88%
“…Both results were then compared to determine the load capacity loss after installing the opening, and these results served as a baseline for choosing working load values of other un-strengthened walls with various openings. Furthermore, the findings of Behfarnia et al [39] were helpful for estimating the working load values; for walls with an opening area of 6.25%, the working load was about (50-75%) of the ultimate load of control shear wall; for walls with an opening area of 11.11%, the working load was approximately (40-50%) of ultimate load of control shear wall; and for walls with an opening area of 25%, the working load was about (30-40%) of ultimate load of control shear wall, and considering the above-mentioned data and the appearance of developed diagonal cracks on each wall specimen, the working load value was carefully selected.…”
Section: Casting and Testing Proceduresmentioning
confidence: 93%
See 1 more Smart Citation
“…It was found that the bearing capacity of the shear walls with openings was improved with CFRP reinforcement and consequently with reduction of active stresses in the upper corner of the opening. Behfarnia and Sayah (2012) conducted theoretical studies on the impact of openings in shear walls reinforced with FRP sheets. Their results showed that the CFRP sheets caused maximum reinforcement in shear walls with opening with an area of 25% (relative to the total area of the wall) associated with 39% increase in capacity.…”
Section: Introductionmentioning
confidence: 99%